Diffusion-weighted imaging lesions and risk of recurrent stroke after intracerebral haemorrhage. Issue 9 (8th June 2021) - Wiegertjes, Kim; Dinsmore, Lynn; Drever, Jonathan; Hutchison, Aidan; Stephen, Jacqueline; Valdés Hernández, Maria C; Bhatnagar, Priya; Minks, David P; Rodrigues, Mark A; Werring, David J; de Leeuw, Frank-Erik; Klijn, Catharina JM; et al.
Abstract : Objective: To determine whether the presence of diffusion-weighted imaging-positive (DWI+) lesions is associated with recurrent stroke after intracerebral haemorrhage (ICH). Methods: The REstart or STop Antithrombotics Randomised Trial (RESTART) assessed the effect of restarting versus avoiding antiplatelet therapy after ICH on major vascular events for up to 5 years. We rated DWI sequences of MRI done before randomisation for DWI+ lesion presence, masked to outcome and antiplatelet use. Cox proportional hazards regression models were used to quantify associations. Results: Of 537 participants in RESTART, 247 (median (IQR) age 75.7 (69.6–81.1) years; 170 men (68.8%); 120 started vs 127 avoided antiplatelet therapy) had DWI sequences on brain MRI at a median of 57 days (IQR 19–103) after ICH, of whom 73 (30%) had one or more DWI+ lesion. During a median follow-up of 2 years (1–3), 18 participants had recurrent ICH and 21 had ischaemic stroke. DWI+ lesion presence was associated with all stroke, (adjusted HR 2.2 (95% CI 1.1 to 4.2)) and recurrent ICH (4.8 (95% CI 1.8 to 13.2)), but not ischaemic stroke (0.9 (95% CI 0.3 to 2.5)). DWI+ lesion presence (0.5 (95% CI 0.2 to 1.3)) vs absence (0.6 (95% CI 0.3 to 1.5), pinteraction =0.66) did not modify the effect of antiplatelet therapy on a composite outcome of recurrent stroke. Conclusions: DWI+ lesion presence in ICH survivors is associated with recurrent ICH, but not with ischaemic stroke. We found no evidence of modification of effects of antiplatelet therapy on recurrent stroke after ICH by DWI+ lesion presence. These findings provide a new perspective on the significance of DWI+ lesions, which may be markers of microvascular mechanisms associated with recurrent ICH. Trial registration number: ISRCTN71907627 .